THE INFLUENCE OF COOPERATIVE LEARNING MODELS WITH A CONTEXTUAL TEACHING AND LEARNING APPROACH ON STUDENT LEARNING OUTCOMES IN ECONOMIC SUBJECTS - Wati, Rahma; Oknaryana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2025)
This study is based on the need to improve student learning outcomes in economics through the application of effective learning models, especially those that can relate economic concepts to real-life situations experienced by students in their daily lives. This study aims to examine the impact of cooperative learning models integrated with the Contextual Teaching and Learning (CTL) approach on students’ academic performance in economics. This study uses an experimental design with a quantitative approach. The design applied is a nonequivalent control group design, involving two groups of 11th grade high school students an experimental group using the cooperative model with the CTL approach and a control group using the conventional learning model. Economics achievement data were obtained through testing and analyzed using an independent sample t-test. The analysis revealed a significance value of 0.000, which is lower than 0.05, indicating that students taught using the cooperative learning model with a CTL approach achieved higher learning outcomes compared to those taught through conventional methods. The findings suggest that applying cooperative learning in conjunction with CTL is effective in enhancing students’ performance in economics. Moreover, this research contributes to the development of learning strategies that are more contextual, engaging, and responsive to students’ individual needs and characteristics.